O CONSUMO CONSCIENTE: DIRETRIZES PARA PRÁTICAS EMPRESARIAIS - Alves, Sebastião Luiz (2012)
This research aims to investigate and introduce the sustainable practices that companies are promoting to their workforce in order to make you aware and achieve a reduction in waste and therefore of the costs caused by them. To achieve this goal, a content analysis method was used , based on a bibliographical qualitative research , through the reading and analysis of scientific texts related to social responsibility, sustainability and ethical consumerism , in other words an exploration of secondary sources in order to develop the study. A literature review was conducted to discuss the reality of social responsibility, sustainable development and business practices associated with the concepts of ethical consumerism towards the workforce. The research methodology was qualitative, exploratory and based on secondary data. These Secondary data were extracted from scientific articles, which bring cases of companies considered socially and environmentally responsible which practice and preach ethical consumerism with its workforce. The results are presented in a list of guidelines: indicate the organizational social responsibility, applied internally as ethical consumerism program. The list consists of general and specific guidelines, in form of recommendations identified in the cases of the analyzed business practices.